TANGGUNG JAWAB KURATOR DALAM PENGURUSAN DAN PEMBERESAN HARTA PAILIT DI KABUPATEN BADUNG - Wiranegara Wesna, Made Bagoes; Dunia, Ngakan Ketut; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
In the business world, both individuals and businesses with legal status does notalways go smoothly, there are times when the company is losing money and can’t payits debts to creditors. The company are not able to pay its debts may be petitioned forbankruptcy by its creditors or its own pleading for bankruptcy. Following the decisionof the Commercial Court decided by the company (debtor) can’t manage his owncompany property hereinafter called the bankruptcy estate, but by the Curator who didthe management responsibility and settlement of the bankruptcy estate pursuant to ActNo. 37 of 2004 on Bankruptcy and Suspension Debt obligations.
Keywords: Responsibility, Curator, Management of Bankruptcy